473 COMPLIANCE WITH EVIDENCE-BASED GUIDELINES DECREASES READMISSIONS FOR CHILDREN WITH ASTHMA EXACERBATIONS. Issue 1 (1st January 2007) - Fassl, B.; Nkoy, F.; Srivastava, R.; Stone, B.; Maloney, C.
Abstract : Study Purpose: Pediatric asthma care remains a significant burden for patients, families, and the health care system. The objectives were to assess provider compliance with evidence-based recommendations regarding appropriate inpatient asthma care and to determine its effect on readmission rates. Methods: Retrospective study of 101 consecutive admissions in 2005 of children admitted for asthma exacerbations to the study hospital. Data were obtained through manual chart review. Provider compliance with two known evidence level A recommendations was assessed. These recommendations are documentation of chronic asthma symptoms and severity and discontinuation of ipatropium bromide 24 hours after admission. Results: Nineteen percent of children were assessed for the presence/degree of chronic asthma symptoms and severity. Twenty-four percent of children received ipratropium bromide for longer than 24 hours after admission. Readmission rates for children whose chronic asthma severity assessment was documented were lower (11% vs 15%, p < .01) compared with those children who did not have such documentation. Conclusions: Provider compliance with evidence-based recommendations remains low. Children whose chronic asthma symptoms were assessed were less likely to be readmitted within 6 months. Quality of inpatient pediatric asthma care could be improved through increased compliance with evidence-based recommendations. New strategies are needed to enforce compliance among the physicians.